2017
DOI: 10.1002/ange.201708790
|View full text |Cite
|
Sign up to set email alerts
|

Bioorthogonal Click and Release Reaction of Iminosydnones with Cycloalkynes

Abstract: We report the discovery of a new bioorthogonal click‐and‐release reaction involving iminosydnones and strained alkynes. This transformation leads to two products resulting from the ligation and fragmentation of iminosydnones under physiological conditions. Optimized iminosydnones were successfully used to design innovative cleavable linkers for protein modification, thus opening up new areas in the fields of drug release and target‐fishing applications. This click‐and‐release technology offers the possibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…To overcome this limitation, we envisaged that sialic acids fitted with a sydnone moiety, an aromatic mesoionic 1,3‐dipole, would be valuable unnatural sugars for addition to the MOE toolbox. We and others have recently shown that sydnones can react in a metal‐free strain‐promoted click fashion with cyclooctyne reagents for the in vitro bioconjugation of purified proteins …”
Section: Figurementioning
confidence: 99%
“…To overcome this limitation, we envisaged that sialic acids fitted with a sydnone moiety, an aromatic mesoionic 1,3‐dipole, would be valuable unnatural sugars for addition to the MOE toolbox. We and others have recently shown that sydnones can react in a metal‐free strain‐promoted click fashion with cyclooctyne reagents for the in vitro bioconjugation of purified proteins …”
Section: Figurementioning
confidence: 99%
“…An interesting finding can be highlighted from this study: substituents on position N 6 play a considerable role with respect to the reaction rate of the transformation. As we previously described, amide‐substituted ImSyd 5 a – d and carbamate derivatives 7 a , b are competent substrates but with moderate reactivity (0.004< k <0.018 m −1 sec −1 ). The presence of a more electron‐withdrawing sulfonamide moiety on the other hand increases the rate up to 0.042 m −1 sec −1 for compound 6 b .…”
Section: Methodsmentioning
confidence: 61%
“…[b] The rate constants were determined under initial rate conditions. Kinetic results of compounds 4 a , 5 a , 6 a , 7 b , 8 a , 8 i and 9 f were described in our previous paper …”
Section: Methodsmentioning
confidence: 89%
See 2 more Smart Citations